Nitrogen Fertilizer Use Efficiency in Winter Wheat Trials (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
The field experiments with ten diverse varieties of winter wheat were laid down according to uniform scheme during 2001 – 2002 at three locations having different soils and agroclimatic conditions: study and research farm “Pēterlauki” of the Latvia University of Agriculture on sod – calcareous medium loam soils, humus content 19 – 21 g kg-1 of soil; at the Stende Plant Breeding Station on sod – podzolio soils, humus content 18 - 19 g kg-1 of soil and at Latgale Science Centre in Viļāni on humus – podzolic gley soils, humus content 65 – 95 g kg-1 of soil. There was observed sharp variation in meteorological conditions during experimental years and quite variable weather conditions between the trial sites. The average results obtained in the experiments suggest that stable increase of winter wheat grain yield was reached increasing fertilizer N rates from N90 to N120 (split application) thus ensuring grain yield increase 1 to 20 kg per 1 kg N applied. The crude protein yield 2,8 – 3,47 kg per 1 kg N applied was obtained from trial plots at the study and research farm “Pēterlauki” and at the Stende Plant Breeding Station. The mineral N use efficiency was considerably lower in humus – rich soils in Viļāni. The increase of fertilizer N rate up to N180 (split application) resulted in gradual decrease of nitrogen use efficiency, and utilization coefficient was to a great extent depended on meteorological conditions during vegetation period.